Tuned Mass Dampers for Response Reduction of a Reinforced Concrete Chimney Under Near-Fault Pulse-Like Ground Motions - Elias, Said; Rupakhety, Rajesh; Ólafsson, Simon (Frontiers in Built Environment, 2020)
The article investigates response mitigation of a reinforced concrete (RC) chimney subjected to pulse-like near-fault ground motions using tuned mass damper (TMD) schemes. The total height of the chimney is 265 m with a mass of 11,109 ton. Three TMD schemes are used: single tuned mass damper (STMD), multiple TMDs having equal stiffness (w-MTMDs) and multiple TMDs having equal masses (e-MTMDs). The STMD is tuned to the fundamental frequency of the chimney while both w-MTMDs and e-MTMDs have three TMDs for controlling each of the first and second modes (total of six TMDs) of vibration. Response of the uncontrolled and controlled structures is calculated for 69 recorded ground motions containing a dominant velocity pulse. Displacement and acceleration at top node of the RC chimney are the response of interest for performance assessment. It is found that e-MTMDs are more effective and robust than other schemes. It is also found that the pulse period of ground motion plays a very important role in how effective the control schemes are. There is a large variability in the reduction of response across these ground motions, and optimization methods independent of ground motion are not robust. There is a need for more advanced optimization methods incorporating information about local seismic sources.